ESTIMATION OF FISHERY RESOURCES BY M-F GIS USING SATELLITE DATA AND ITS APPLICATION TO TAC FOR SUSTAINABLE FISHERY PRODUCTION - Yasuhiro Sugimori; Takashi Moriyama; Bambang Tejasukmana; Indroyono Susilo; Ketut Swardika (International Journal of Remote Sensing and Earth Sciences (IJReSES), 2006)
-